Emergency Detection and Monitoring Daily Routine of a Cattle using IOT - Chandana R,; Nagapragathi S V,; Nagashree B K,; Pooja Manjunath,; Mr. Kiran Kumar T, (Journal of Electronic Design Engineering, 2019)
The main aim of this system is to smarten the infrastructure of cattle farming and to track the biological and physiological activities of cattle by implementing a noninvasive wearable by using IOT. In these, we come into picture the lightning sensor depend upon the climate it will turn on and off, temperature sensor will depend upon room temperature of cattle farm; methane sensor is used to check methane level in the farm; fire sensor depend upon any fire emergency and is responsible for smart lighting and also smart ventilation, it is also responsible for sprinkler actuation to make the infrastructure safer and smarter. We are also implementing automatic food releasing mechanism. We can identify the single cattle count with the help of the IR sensor.